ETNOBATANI MASYARAKAT O HONGANA MA NYAWA DI DESA WANGONGIRA, KABUPATEN HALMAHERA UTARA - Radios Simanjuntak; Ervizal A.M. Zuhud; Agus Hikmat (Department of Forest Resources Conservation and Ecotourism - IPB University, 2015)
O hongana ma nyawa is a community who used to live nomadically in the Forest of Halmahera Island by hunter and gather. Most of them have been resettled by the Indonesian government. Ethnobotany research to analyse the diversity of plants used by those community who live in Wangongira village, North Halmahera regency, was conducted on April to Mai 2015. A total of 153 used plant species of 54 families are identified, most of them are wild plants and taken from the forest. Most of the plants species used that are coming from the forest show their high knowledge of forest products nevertheless they have been resettled for years. Keywords: ethnobotany, North Halmahera, O hongana ma nyawa, plant species diversity, utilization knowledge